An Overview of Systematic Reviews of Herbal Medicine for Irritable Bowel Syndrome - Jun, Hyejin; Ko, Seok-Jae; Kim, Keumji; Kim, Jinsung; Park, Jae-Woo (Frontiers in Pharmacology, 2022)
Background: Irritable bowel syndrome (IBS) is a common disorder with abdominal pain and bowel habits changes. Herbal medicines (HMs) are frequently used in the treatment of IBS. Therefore, several systematic reviews (SRs) have been conducted to assess the efficacy and safety of HM in IBS patients. This study aimed to investigate the methodology and quality of evidence of SRs, and to describe the current state of research and evidence for the treatment of IBS with HM. Methods: SRs published up to January 2022 were searched using six electronic databases. SRs and/or meta-analyses on the use of HMs for IBS were included. The effects of placebo, conventional medicine (CM), and probiotics were compared with those of HMs. Two investigators independently extracted the data and assessed methodological quality using the Measure Tool to Assessment System Reviews 2 (AMSTAR 2). Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) was used to evaluate the quality of evidence for each main finding. Results: Eighteen SRs were included in this overview. Among them, eight SRs reported only specific subtypes of IBS: six SRs reported patients with diarrhea-predominant IBS, and two SRs reported patients with constipation-predominant IBS. In terms of total efficacy, HM was more effective than placebo, CM, or probiotics. HM showed a more significant effect than CM in relieving independent IBS symptom score (abdominal pain score, diarrhea score, abdominal distension score, stool frequency score, etc.) and recurrence rate. The rate of adverse events was significantly lower with HM compared to CM, and no serious adverse events were reported with HM treatment. According to AMSTAR 2, the methodological quality of the included SRs was extremely low. Furthermore, the quality of evidence for total efficacy was considered low or very low according to the GRADE tool. Conclusion: HM can be considered as an effective and safe treatment for IBS. However, the methodological quality of the included SRs and the quality of evidence was generally low. Therefore, well-designed randomized controlled trials are needed in the future so that a high-quality SR can be used to better assess the safety and efficacy of HM in the treatment of IBS.